UMP researchers won three gold medals, three silver medals and four bronze medals at the BioMalaysia Exhibition 2013 in Persada, Johor Bharu. - Noor Syahidah, Sabran (Penerbit UMP, 2013)
Universiti Malaysia Pahang (UMP) collected three gold medals, three silver medals and four bronze medals out of the 11 entries submitted in the BioMalaysia Exhibition 2013 of Persada International Convention Centre in Johor Bahru.